Threat for the survival of wildlife in and around the Desert National Park of Rajasthan - Vijay Kumar,; Devendra Singh Chouhan, (The Bioscan, 2025)
Study was conducted in Desert National Park and its peripheral areas in western Rajasthan to assess threats and conservation problems for the survival of wildlife species from June 2023 to May 2025. Study was conducted with the help of line transect, road transect, direct observation, random opportunistic sampling methods, and schedule survey methods to assess major threats to wildlife survival. Numerous anthropogenic activities, such as illegal grazing, framing, agricultural activity in protected areas, poaching, hunting, disturbance and collection of plant-based products have been observed. Additionally, the replacement of wooden or thorn fencing with iron net fencing also affects the survival of several wildlife species, especially large body-sized animals. Furthermore, Iron net fencing acts as a trapping net and barrier for species movement from one area to adjoining area, as well as reduces habitat availability for cryptic and burrow-dwelling wildlife. Another threat in this region is that the rapidly growing free-ranging dogs pose a substantial threat to wildlife survival. Rapid expansion of liner infrastructure, such as roads, state, and national highways in the western Thar Desert region, has largely contributed to the increasing incidence of wildlife mortality. Water shortages in desert regions pose significant challenges for wildlife survival, affecting various aspects such as the daily need for water intake. Installation of wind turbines and high-tension electric power lines throughout desert regions are largely responsible for the death of numerous bird species. Extensive networks of Indra Gandhi Nahar Pariyojna (IGNP) desert regions have rapidly converted desert areas into agricultural and farmland habitats. Invasion by exotic species significantly affects the habitat characteristics of desert ecosystems.